Immersive Data Analysis for Planning Military Operations: Design and Think-Aloud Study - Neto, Jerson; Secco, Otávio; Freitas, Carla; Wagner, Jorge; Maciel, Anderson; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
The ability to visualize data in immersive environments offers new interpretations that directly impact the outcomes of activities such as military planning, where effective decision-making is vital for mission execution. This work aims to explore the application of VR in military planning as a tool that exploits a metaphor of the sandbox, the current planning approach adding increased possibilities of visualizing training range data in 3D. To achieve this, we designed and developed a prototype that includes a virtual terrain and miniature models and provides interactions based on the sandbox concept. To evaluate the prototype, a user study was conducted with army experts performing a planning task using both conventional methods and VR. Results indicate that VR is a viable alternative with an impact on the decision-making process during military planning. Future research should focus on assessing the effects of multiple conditions with a larger group of participants and investigating additional functionalities such as spatial perception.